Analysis of Super Rugby from 2011 to 2015 - Schoeman, R.; Coetzee, D.; Schall, R. (International Journal of Performance Analysis in Sport, 2017)
Rugby shows proof of evolution within the professional era due to large contributions from technology and improved training. Evidence of evolution can be traced through statistics. Therefore, the aim of this study was to compare match activities over five seasons (2011-2015) of Super Rugby matches played, and to investigate performance indicators that allow discrimination between winning and losing teams. Data from 30 matches per season (4 matches from each of the 15 participating teams) were captured and supplied by the Cheetahs Super Rugby Franchise (Bloemfontein, South Africa), using the Verusco TryMaker Pro. Differences in mean rates were found between seasons and between winning and losing teams. Losing teams showed an increase in rucks and mauls, lost more scrums and missed more tackles. Playing time, scrums lost and penalties decreased from 2011 to 2015, while scrums (1.76%), rucks (0.80%), mauls (4.42%) and tackles (1.07%) showed a slight increase. Significant differences were found for line-outs (mean of 3.5% per year; 95% confidence interval (CI) 0.7-6.5%; p = 0.0156) and tackles missed (5.7%; 95% CI 3.0-8.4%; p = <0.001). The findings agree with previous research, that most changes can be contributed to the physiological improvement of players and the increased emphasis on perfecting set phases.